Life-drawing : trauma and intimacy in the essay qua drawing : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Fine Arts, Massey University Te Kunenga ki Pūrehuroa, Te Whanganui-a-Tara Wellington, Aotearoa New Zealand - Amodeo, Gabrielle (Massey University, 2022)
Developing from a foundation of practice that included expanded field of drawing explorations, installation, and texts presented with gallery-based exhibiting, this research asks how an expanded practice of life-drawing—in which the essay operates in the capacity of a drawing—is valuable as a mode of representing experiences of trauma and intimacy within a contemporary visual arts context. Through an engagement with autotheoretical practices, and through proposing the form of an expanded practice of life-drawing (as a parallel to life-writing), this research investigates the theorised experiences of trauma and intimacy, both separately and in tandem, as they relate to drawing and the essay. It particularly looks at the dissociation of trauma in comparison, and in relation to, accrued observation as a practice of intimacy. This research also explicates the similarities between the essay and drawing, similarities that pull them so close, the essay can be sited within an expanded definition of drawing. To argue this, it investigates the effect of conceptual art and related commentaries on loosening understandings of drawing particularly, and art disciplines generally, away from traditional material concerns, allowing space for the essay in the capacity of a drawing. It then proposes the essay qua drawing as valuable in embodying the relationship between dissociation and intimacy. The essay qua drawing addresses the way drawings and essays can inform, exacerbate, disrupt and enhance the experience of trauma and intimacy. Both drawing and the essay are almost definitionally involved with forms that relate to the experience of trauma (in particular, gap and fragment) and the experience of intimacy (as a practice of accrued observation). The outcome is a novella-length personal essay presented in a limited-edition book that, in style, sits between artist-book and commercially published book.
Figures are re-used with permission.
Listed in 2023 Dean's List of Exceptional Theses
Keywords: Drawing; Essay; Psychic trauma in art; Intimacy (Psychology) in art; Dean's List of Exceptional Theses; 369999 Other creative arts and writing not elsewhere classified